PENTINGNYA PEMAHAMAN HUKUM UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM ERA DIGITAL - Sitio, Befri Antono; Laia, Aturkian (JURNAL PANAH KEADILAN, 2024)
The development of information and communication technology (ICT) has changed various aspects of human life, making understanding the laws governing the use of this technology, such as the Information and Electronic Transactions Law (UU ITE), very important. The ITE Law in Indonesia, which was passed in 2008, was revised in 2016. The second amendment in 2024 regulates various aspects ranging from electronic transactions to criminal sanctions for misuse of information technology. A good understanding of the ITE Law can provide legal protection, create safe transactions, prevent violations, and increase people's digital literacy. Violations of the ITE Law can result in legal sanctions, financial losses, reputation damage, and threats to data security. This article highlights the importance of education and understanding of the ITE Law to build a safe and responsible digital ecosystem.